Diversity of coral reef fishes in Cuddalore waters, south-east coast of India - S, Ajmal Khan (Indian Journal of Fisheries, 2011)
The present study was undertaken to obtain basic information on the diversity and species richness of coral reef fishes inCuddalore waters. Based on collections made for a period of one year, the study has brought to light the occurrence of25 species of colourful fishes belonging to 16 families. Among the 25 species,Upeneus vittatus was found to be the mostdominant species (27.5%). The values of Shannon diversity (log2) index, Margalef richness, Simpson richness and Pielou'sevenness during the four seasons covered, varied from 3.3 to 3.9; 2.2 to 3.0; 0.8 to 0.9 and 0.8 to 0.84 respectively. Themaximum diversity and richness were recorded during the pre-monsoon season and the lowest during the monsoon season.However, these conventional indices could not effectively bring out the differences in diversity between the seasons as thevalues ranged narrowly. The recently introduced taxonomic diversity index which ranged from 83.7 to 76.0 was found to beeffective. But the difference between summer (76.8) and monsoon (76.0) seasons with 19 and 15 species respectively wasnot distinct. The variation in taxonomic distinctness index (range: 298.9-131.6) and total phylogenetic diversity index (range:2033.3-1166. 7) effectively brought out the differences between the seasons underscoring the advantage of using thesediversity indices for biodiversity assessment. Further, the present study underlines the need for making a detailed investigationon the biodiversity of fishes occurring in the reef patches reported off Cuddalore, Parangipettai and Pondicherry making useof visual census method.